2021
DOI: 10.21203/rs.3.rs-301541/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterisation of tumour immune microenvironment remodelling following oncogene inhibition in preclinical studies using an optimised imaging mass cytometry workflow

Abstract: Mouse models are critical in pre-clinical studies of cancer therapy, allowing dissection of mechanisms through chemical and genetic manipulations that are not feasible in the clinical setting. In studies of the tumour microenvironment (TME), novel highly multiplexed imaging methods can provide a rich source of information. However, the application of such technologies in mouse tissues is still in its infancy. Here we present a workflow for studying the TME using imaging mass cytometry with a panel of 27 antibo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…4A). Using IMC, we recently showed that there was an inclusion of macrophages and neutrophils in the core of 3LL ΔNRAS lung tumors, while effector cells remained at the tumor periphery ( 21 ). Consistent with this apparent immunosuppressive TME, growth of these tumors was not affected by a lack of B and T cells in Rag1 −/− mice (fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…4A). Using IMC, we recently showed that there was an inclusion of macrophages and neutrophils in the core of 3LL ΔNRAS lung tumors, while effector cells remained at the tumor periphery ( 21 ). Consistent with this apparent immunosuppressive TME, growth of these tumors was not affected by a lack of B and T cells in Rag1 −/− mice (fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, similarly to other targeted therapies, early clinical results indicate that drug resistance frequently arises, resulting in clinical relapses ( 11 , 12 ). KRAS G12C inhibitors not only affect the survival of cancer cells but also can mediate immunomodulatory effects by reversing KRAS-driven immunosuppressive mechanisms and generate a TME that is more favorable for an antitumor immune response ( 8 , 19 , 21 ). This knowledge has served as a rationale to investigate clinical combinations of KRAS G12C inhibitors with anti-PD1 or PD-L1 antibodies ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently available tools are technology-specific and cover only some steps of the whole analytical workflow (Table 1). For example, several computational approaches have been developed to process raw images and extract single-cell data either interactively (Ilastik 10 , CellProfiler4 11 , CODEX Toolkit 4 ) or via command line (imcyto 12 , ImcSegmentationPipeline 13 ). Distinct sets of tools can then perform cell phenotyping (CellProfiler Analyst 14 , Cytomapper 15 , Immunocluster 16 ) or analyse cell-cell spatial interactions (CytoMap 17 , ImaCytE 18 , SPIAT 19 , neighbouRhood 20 ).…”
Section: Mainmentioning
confidence: 99%